Serum eosinopholic cationic protein (ECP) in asthmatic Malaysian children - Chan, P.W.K.; Samsinah, H.H.; Arpin, H.Z.; Mustafa, A.M.; Bruyne, J.A.D. (Malaysian Medical Association, 2002)
Eosinopholic inflammation in the airways is important in the pathogenesis of childhood asthma. Serum eosinopholic cationic protein (ESP), a marker of eosinophil activation was measured in 20 asthmatic smoke esposure, urinary cotinine levels and family history of asthma between the two groups. The median serum ECP in asthmatic children was 27.0 mcg/L (IQ1 8.8, IQ3 59.0); which was higher than in non-asthmatic controls 5.9 mcg/L (IQ1 3.0, IQ3 11.9), p=0.0021. An elevated serum ECP level can be helpful as supportive evidence in the diagnosis of bronchial asthma in Malaysia children